The Essence of Cryptocurrency, Its Advantages and Disadvantages ("Journal "U". Economy. Management. Finance.", 2020)
A comprehensive author's study of the essence of cryptocurrency, its advantages and disadvantages. Assessing the importance of its application in the modern world and developing a strategy for introducing cryptocurrencies into everyday life.
Keywords: cryptocurrency; blockchain; transaction; currency